2006
DOI: 10.1021/jf061789l
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Glucosinolates in Pickling Cruciferous Vegetables

Abstract: Crucifer species, which include widely consumed vegetables, contain glucosinolates as secondary metabolites. Cruciferous vegetables are consumed in Japan in salt-preserved or pickled form as well as cooked and raw fresh vegetables. In this study, changes in contents of glucosinolates during the pickling process were investigated. 4-Methylthio-3-butenyl glucosinolate, a major glucosinolate in the root of Japanese radish, daikon (Raphanus sativus L.), was detected in pickled products with a short maturation peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…In another study, MTBGLS was detected in commercial takuan-zuke with a short maturation period, and not detected in that with a long maturation period. 16) In the present study, MTBGLS in the radish disappeared during 1-mo salting after dehydration (data not shown). The amount of MTBGLS was equivalent to 52.8 μmol/g on the scale of dry weight.…”
Section: Salting Time (Mos)supporting
confidence: 38%
“…In another study, MTBGLS was detected in commercial takuan-zuke with a short maturation period, and not detected in that with a long maturation period. 16) In the present study, MTBGLS in the radish disappeared during 1-mo salting after dehydration (data not shown). The amount of MTBGLS was equivalent to 52.8 μmol/g on the scale of dry weight.…”
Section: Salting Time (Mos)supporting
confidence: 38%
“…Blanching is considered as a pre-treatment for industrial processing (Fellows, 2000). It was applied on Brassica vegetables prior to pickling (Suzuki et al, 2006), freezing, and frozen storage (Rodrigues and Rosa, 1999;Rungapamestry et al, 2008) to reduce further degradation of GLSs during the core processing. Blanching of Brassica vegetable aims to inactivate myrosinase and consequently, can inhibit the GLS enzymatic hydrolysis.…”
Section: Blanchingmentioning
confidence: 99%
“…Mechanisms affecting GLS content differ from processing by applying heat; however, to our knowledge these are scarcely studied. Bacteria and sodium chloride might take significant role to change the GLSs during fermentation (Tolonen et al, 2002;Suzuki et al, 2006). Suzuki et al (2006) examined in vitro myrosinase activity against sinigrin at various levels of NaCl and pH.…”
Section: Fermentationmentioning
confidence: 99%
“…MTBITC. MTBITC is an efficient anti-oxidant and scavenger of oxygen free radicals; its antioxidant activity is greater than that seen with ascorbic acid or vitamin E (Suzuki et al, 2006). Compositional analyses of the TRE (Ben Salah- Abbès et al, 2008b) has revealed that there are significant quantities of several important phenolic agents, such as gallic acid, ferulic acid, isoferulic acid, sinapic acid, methyl ferulate, methylsinapate, and 4-(methylthio)-3-butenyl isothiocyanate (MTBITC), as well as the parent glucosinolate of MTBITC.…”
Section: Immunoglobulin µG/mlmentioning
confidence: 99%